MODELING QUALITY EDUCATION IN A STATE UNIVERSITY - Flores, Abel Alejandro U. (International Journal of Research -GRANTHAALAYAH, 2019)
An exploration and analysis of the processes involved in crafting the institution’s strategic plan, identifying its quality assurance policies, documenting its graduates’ performance in government licensure examinations, description of the processes to ensure sustainability of educational programs, and portray the administration’s fund generation and management mechanisms was made in an effort to create a model for quality education in the University of Eastern Philippines, University Town, Northern Samar. It utilized the descriptive-evaluative method of research with a total of 400 respondents composed of students, faculty members, alumni, community residents, and University officials. Qualitative data were taken from respondents’ answers to open-ended questions, which were then validated through interviews. Quantitative data on the other hand, were taken from both primary data derived from responses to items in the questionnaire, and secondary data on graduates’ performance in professional examinations. It was revealed that most stakeholders were aware of the institution’s strategic plan, although some were not consulted in the crafting of such an important document. They aver that policies and guidelines are established, implemented, and strictly adhered to by the administration in its daily operations involving faculty, students, staff, fund generation and management, instruction, research, extension, production, faculty development, and student support services. Although graduates performed consistently well in some government examinations, in the years 2009 – 2014 they performed generally below the national average. Respondents agree that curricular programs must regularly be updated to conform to minimum standards set by the Commission on Higher Education to ensure sustainability of programs. For students to be globally relevant and competent, respondents agree to the provision of educationally qualified and competent teaching force, state-of-the-art facilities, modern instructional materials and methods, coupled with good governance and cooperation among stakeholders, are the key ingredients of an ideal quality of education in the University of Eastern Philippines.